The role of fibrosis, inflammation, and congestion biomarkers for outcome prediction in candidates to cardiac resynchronization therapy: is “response” the right answer? - Beltrami, Matteo; Galluzzo, Alessandro; Brocci, Riccardo Tappa; Paoletti Perini, Alessandro; Pieragnoli, Paolo; Garofalo, Manuel; Halasz, Geza; Milli, Massimo; Barilli, Maria; Palazzuoli, Alberto (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiac resynchronization therapy (CRT) is an established treatment in selected heart failure patients with reduced ejection fraction (HFrEF). It has been proposed that myocardial fibrosis and inflammation could influence CRT “response” and outcome. Our study investigated the long-term prognostic significance of cardiac biomarkers in HFrEF patients with an indication for CRT. Methods: Consecutive patients referred for CRT implantation were retrospectively evaluated. Soluble suppression of tumorigenicity (sST2), Galectin 3 (Gal-3), NT-proBNP and estimated Glomerular Filtration Rate (eGFR) were measured at baseline and after 1 year of follow-up. Multivariate analyses were performed to evaluate their correlation with the primary composite outcome of cardiovascular mortality and heart failure hospitalizations at a mean follow-up of 9+2 years. Results: among 86 patients enrolled, 44% experienced the primary outcome. In this group, the mean baseline values of NT-proBNP, Gal-3 and sST2 were significantly higher compared to patients without CV events. At the multivariate analyses, baseline Gal-3 (cut-off: 16.6 ng/ml, AUC: 0.91, p<0.001, HR 8.33 (1.88-33.33), p=0.005) and sST2 (cut-off: 35.6 ng/ml AUC: 0.91, p<0.001, HR 333 (250-1000), p=0.003) significantly correlated with the composite outcome in prediction models with high likelihood. Among parameters evaluated at 1 year follow-up, sST2, eGFR and the variation from baseline to one-year levels of Gal-3 showed a strong association with the primary outcome (HR 1.15 (1.08-1.22), p<0.001; HR: 0.82 (0.75-0.90), p=0.04; HR: 1.28 (1.11-1.48), p=0.001, respectively). Conversely, the echocardiographic definition of CRT response did not correlate with any outcome. Conclusion: in HFrEF patients with CRT, sST2, Gal-3 and renal function were associated with the combined endpoint of cardiovascular death and HF hospitalizations at long-term follow-up, while echocardiographic CRT response did not seem to influence patients’ outcome.